Teachers' narratives of their experience of teaching Fetal Alcohol Spectrum Disorders (FASD) -affected children in mainstream schooling - Makasi-Simukonda, Mihlali (Rhodes University, Faculty of Humanities, Department of Psychology)
This study considers the experiences of teachers working with Fetal Alcohol Spectrum Disorders (FASD)-affected children in mainstream schooling. FASD refers to a range of conditions in children resulting from maternal alcohol consumption during pregnancy. Prevalence rates in South Africa are said to be among the highest in the world. There is a paucity of research on FASD-affected children in the Eastern Cape. This study was thus conducted in the Buffalo City Metropolitan Municipality (BCMM). Teachers told stories of their experiences of teaching undiagnosed FASD-affected children in mainstream schooling. The stories reveal the quality of life for children in classrooms and socio-contextual influences of their experiences at school, as well as the responsibilisation of teachers in these settings. This qualitative research is situated within a social constructionism paradigm. The social model of disability was utilised as a theoretical framework for this study to represent the systemic barriers against which FASD-affected learner support in the mainstream school can be conceptualised. A sample of five (5) Black female teachers were interviewed. Data gathering was done by conducting telephonic interviews using the single question inducing narrative, known as SQUIN. A thematic analysis of the data was conducted for the purpose of identifying themes within the data collected. Four superordinate themes emerged from the data, viz. narratives of FASD-affected learners, narratives of parental involvement, narratives of the role of teachers and narratives of stakeholder support. This study reveals a significant level of responsibilisation of teachers. Teachers appear to play a bigger role than just being teachers and they positioned themselves as playing a parental role in relation to FASD-affected learners. FASD-affected learners were positioned as "the problem" in the mainstream classroom whereas the environment is a disabling factor to FASD-affected learners. There is a need for a holistic approach in working with FASD-affected learners from all relevant stakeholders. Key recommendations are made for effective inclusion of FASD-affected learners in mainstream schooling. Future research recommendations include repeating this study in a different geographical area, a focus on senior phase learners and/or a more diverse sample. The findings assist in the development of policies of inclusive education in mainstream schooling and supportive strategies to enhance the developmental trajectory of FASD-affected children.
Keywords: Fetal alcohol spectrum disorders -- South Africa Buffalo City; Inclusive education -- South Africa Buffalo City; Teachers of children with disabilities -- South Africa Buffalo City; Children of prenatal alcohol abuse -- South Africa Buffalo City Social conditions; Social constructionism